Sistem Pendukung Keputusan Perdagangan Cryptocurrency Menggunakan Pembobotan Kombinasi Indikator EMA, RSI, MACD, dan Bollinger Bands - M. Zaky Pria Maulana; Rizky Parlika; Firza Prima Aditiawan (JOINS (Journal of Information System), 2026)
Cryptocurrency trading has rapid and significant price changes that cause investors to make decisions based solely on intuition when buying assets, potentially leading to a risk of loss. Therefore, this research aims to develop a cryptocurrency trading decision support system (DSS) using a combination of technical indicators, namely EMA, RSI, MACD, and Bollinger Bands. The system is designed to assist users in making more objective trading decisions based on historical data. This study applies weighted indicator combinations ranging from 0 to 4, resulting in 625 weight combinations evaluated thru backtesting using ROI, Win Rate, and MDD metrics. Based on the test results, the weighted indicator combination outperformed single indicators by achieving an ROI increase of up to 2222.35% on the SOLUSDT asset. In addition, the approach improved signal accuracy, as shown by the increase in Win Rate on ETHUSDT from 35.21% to 47.28% and on SOLUSDT from 32.84% to 58.11%. Furthermore, the method was effective in mitigating risk, indicated by the reduction of MDD on ETHUSDT from 50.04% to 41.35%. The system was successfully implemented as a web-based application integrated with Telegram notifications to deliver analysis results to users.